Aqueous dispersion and electroluminescent element

An aqueous dispersion of solid luminescent metal complexes with a surfactant facilitates the formation of functional layers in electroluminescent devices, overcoming solubility issues and environmental concerns to achieve superior light-emitting performance.

JP7671062B2Active Publication Date: 2025-05-01MEISEI CHEM WORKS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021110151
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-01
Publication Date
2025-05-01
Estimated Expiration
2041-07-01

AI Technical Summary

Technical Problem

Existing methods for forming functional layers in electroluminescent devices using wet methods are hindered by the poor solubility of luminescent metal complexes in organic solvents, leading to insufficient light-emitting properties and increased environmental impact.

Method used

The use of an aqueous dispersion containing solid particles of luminescent metal complexes with aluminum, zinc, or platinum group elements as the central metal, and a surfactant, allows for easy layer formation by a wet method, even with poorly soluble metal complexes.

Benefits of technology

This approach enables the production of electroluminescent devices with excellent light-emitting properties while reducing environmental impact and manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671062000001
    Figure 0007671062000001
  • Figure 0007671062000002
    Figure 0007671062000002
  • Figure 0007671062000003
    Figure 0007671062000003
Patent Text Reader

Abstract

To provide an aqueous dispersion that allows easy formation of a layer by a wet method, a manufacturing method thereof, an electroluminescent device excellent in light emission characteristics, and a manufacturing method thereof.SOLUTION: An aqueous dispersion includes solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as a central metal, and a surfactant. A manufacturing method of an aqueous dispersion includes a step of adding a surfactant and a solid luminescent metal complex to a medium mainly containing water and dispersing the mixture. An electroluminescence device includes a functional layer containing solid particles of a luminescent metal complex having aluminum, zinc or, a platinum group element as a central metal and a surfactant. A manufacturing method of an electroluminescence device includes a step of applying or printing the aqueous dispersion.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electroluminescent device that emits light by converting electrical energy into light. [Background technology]

[0002] Electroluminescent devices (organic electroluminescent devices) that have functional layers such as light-emitting layers and charge transport layers made of organic materials are used as flat panel displays in televisions, mobile terminal displays, lighting, digital signage, etc. In the past, functional layers were formed using dry processes such as vacuum deposition, but in recent years, wet methods such as coating and printing have been attracting attention because of their ease of achieving large areas and their ability to reduce manufacturing costs.

[0003] Regarding the formation of functional layers by wet methods, there are methods in which a coating liquid in which a functional material such as a light-emitting material or a charge transport material is dissolved or dispersed in an organic solvent is used to coat the electrode surface or other functional layers (e.g., Patent Documents 1 and 2). In addition, in consideration of reducing the environmental load and working environment during the manufacture of electroluminescent devices, the formation of functional layers using a coating liquid or an electrolyte solution that uses a medium mainly made of water has also been considered (e.g., Patent Documents 3 to 6). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-96697 A [Patent Document 2] JP 2007-80677 A [Patent Document 3] Special Publication No. 2013-515360 [Patent Document 4] Special Publication No. 2013-515361 [Patent Document 5] Special Publication No. 2013-515362 [Patent Document 6] JP 2015-50448 A Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Documents 1 and 2 disclose a method of coating an electrode surface or other functional layers with a coating liquid in which a functional material is dissolved or dispersed in an organic solvent. However, as described above, the methods described therein are feared to increase the environmental load and deteriorate the working environment. In addition, when such a coating liquid is applied to a pre-formed functional layer to prepare a laminated electroluminescent device, the pre-formed functional layer is invaded and disturbed by the organic solvent contained in the coating liquid, which may result in insufficient light-emitting properties of the obtained electroluminescent device.

[0006] Patent Documents 3 to 5 disclose a method of dissolving a functional material in an organic solvent, dispersing the functional material in a solvent containing a surfactant, and applying the resulting mixture to the surface of an electrode or other functional layers. However, the methods described in these documents could not be applied to luminescent metal complexes that are poorly soluble in organic solvents, such as tris(8-hydroxyquinolinolato)aluminum.

[0007] On the other hand, the solubility can be improved by substituting a bulky alkyl group or the like on a luminescent metal complex that is poorly soluble in an organic solvent, but the alkyl group is insulating, and the mobility of electrons and holes may decrease due to the inhibition of intermolecular contact of aromatic rings, and the manufacturing cost may also increase. Therefore, even when a luminescent metal complex that is poorly soluble in an organic solvent is contained, a technology is required that allows a layer to be easily formed by a wet method.

[0008] Patent Document 6 discloses a method for producing a thin film of a rare earth complex polymer by electrolysis using a mixed micelle-containing solution of a rare earth complex having low solubility in an organic solvent as an electrolyte. However, the method described therein is a complicated method including an electrolysis step, and a functional layer cannot be easily formed by a coating method or the like, and the method can be applied only to specific complex compounds.

[0009] Therefore, the present invention aims to provide an aqueous dispersion and a method for producing the same that can easily form a layer by a wet method even when the aqueous dispersion contains a luminescent metal complex that is poorly soluble in organic solvents, and an electroluminescent device having excellent luminescent properties and a method for producing the same. [Means for solving the problem]

[0010] The above-mentioned problems are basically solved by an aqueous dispersion containing solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as a central metal, and a surfactant.

[0011] Here, the solubility of the luminescent metal complex in chloroform at 22°C is preferably less than 5 g / 100 g-CHCl3. The platinum group element is preferably iridium. The content of the surfactant is preferably 1 to 30 parts by mass per 100 parts by mass of the luminescent metal complex. The surfactant contains a nonionic surfactant and an anionic surfactant, and the amount of the nonionic surfactant in the surfactant is preferably 50% by mass or more, more preferably 70 to 95% by mass. In addition, the surfactant is preferably an ethylene oxide adduct of styrenated phenol.

[0012] The above-mentioned problems can also be solved by a method for producing an aqueous dispersion, which comprises a step of adding a surfactant and a solid luminescent metal complex to a medium mainly composed of water, and dispersing the mixture.

[0013] Furthermore, the above-mentioned problems are also basically solved by an electroluminescent device having, between a pair of electrodes, a functional layer containing solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as a central metal, and a surfactant.

[0014] In addition, the above-mentioned problems are also fundamentally solved by a method for producing an electroluminescent device, comprising a step of coating or printing an aqueous dispersion containing solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as a central metal, and a surfactant. Effect of the Invention

[0015] According to the present invention, it is possible to provide an aqueous dispersion which enables a layer to be easily formed by a wet method and a method for producing the same, and an electroluminescent device having excellent light-emitting properties and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Aqueous dispersion> The aqueous dispersion of the present invention is a fine particle dispersion liquid containing solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as the central metal, and a surfactant in a medium mainly composed of water.

[0017] A medium mainly made of water means a liquid medium containing 50% by mass or more of water, and it is preferable to use water purified by removing impurities as the water to be used. A medium mainly made of water may contain other liquid media in addition to water. Examples of liquid media other than water include water-soluble organic solvents such as monoalcohols, polyhydric alcohols, glycol ethers, and glycol esters, and can be selected from the viewpoints of not increasing the environmental load or worsening the working environment due to volatile vapor or its treatment, and not dissolving or eroding the functional layer previously provided on the electrode, such as a hole transport layer, to be described later, when preparing a laminated electroluminescent device, as required, from the viewpoints of not dissolving or eroding the functional layer previously provided.

[0018] A luminescent metal complex having aluminum, zinc, or a platinum group element as a central metal (hereinafter also referred to as "luminescent metal complex used in the present invention") is a compound that functions as a luminescent material that recombines electrons and holes injected from an electrode and emits fluorescence, phosphorescence, etc.

[0019] As the luminescent metal complex used in the present invention, a material known as a material for an organic EL device can be used, and examples of such metal complex compounds include a metal complex compound in which one or more structures such as oxadiazole, benzoxazole, thiadiazole, benzothiazole, phenylpyridine, phenylbenzimidazole, quinoline, and benzoquinoline are coordinated to a central metal such as aluminum, zinc, or a platinum group element.

[0020] Examples of luminescent metal complexes having aluminum as the central metal include quinoline aluminum complexes such as tris(8-hydroxyquinolinolato)aluminum, tris(4-methyl-8-quinolinolato)aluminum, and tris(5-phenyl-8-quinolinolato)aluminum, aminoquinoline aluminum complexes, and benzoquinoline aluminum complexes.

[0021] Examples of luminescent metal complexes having zinc as the central metal include quinoline zinc complexes such as bis(8-hydroxyquinolinolato)zinc hydrate, benzoquinoline zinc complexes such as bis(10-hydroxybenzo[h]quinolinolato)zinc, benzoxazole zinc complexes, benzothiazole zinc complexes such as bis(2-(2-benzothiazolyl)phenolato)zinc, azomethyl zinc complexes, and porphyrin zinc complexes.

[0022] Examples of luminescent metal complexes having a platinum group element as a central metal include tris(2-phenylpyridinato)ruthenium, tris(2-phenylpyridinato)palladium, octaethylpalladium porphyrin, octaphenylpalladium porphyrin, tris(2-phenylpyridinato)osmium, tris(2-phenylpyridinato)iridium, bis(2-(4,6-difluorophenyl)pyridinato)(picolinato) )iridium, bis(2-(2'-benzo(4,5-α)thienyl)pyridinato)(acetylacetonato)iridium, bis(1-(dibenzo[b,d]furan-4-yl)isoquinolinolato)(1,3-bis(3,4-dibutoxyphenyl)propane-1,3-dionato)iridium, bis(2-phenylpyridinato)platinum, octaethylplatinum porphyrin, octaphenylplatinum porphyrin, and the like. Among these luminescent metal complexes having a platinum group element, metal complexes of iridium are preferred because they have excellent luminescent properties as a phosphorescent material.

[0023] When these are used as light-emitting materials, they can be appropriately selected in consideration of the light-emitting characteristics (light-emitting wavelength, light-emitting efficiency, etc.). In the light-emitting layer of the electroluminescent device, the light-emitting material may be used as a dopant material, and a hole-transporting compound or an electron-transporting compound may be used as a host material. For example, since many of the light-emitting metal complexes used in the present invention have the function of an electron-transporting compound, it is also preferable to use a mixture of an aluminum complex (host material) and an iridium complex (dopant material) as the light-emitting metal complex in the aqueous dispersion of the present invention. The ratio of the dopant material to the host material can be 0.01 to 30% by mass.

[0024] The luminescent metal complex used in the present invention is a solid that is insoluble in water and water-soluble organic solvents such as monoalcohols, polyhydric alcohols, glycol ethers, and glycol esters that can be used as an additive medium as necessary, and therefore the luminescent metal complex exists as solid particles in the aqueous dispersion of the present invention. In addition, many of these are poorly soluble in halogenated hydrocarbon and aromatic organic solvents. Since such luminescent metal complexes that are poorly soluble in organic solvents do not have an unnecessary modifying group such as an insulating alkyl group, the contact between the aromatic rings between molecules is not inhibited, and therefore the mobility of electrons and holes is high, and therefore, by using these, an electroluminescent device with excellent luminescent properties can be obtained. On the other hand, if the luminescent metal complex is poorly soluble in halogenated hydrocarbon and aromatic organic solvents, even if the functional layer of the electroluminescent device is formed using a coating solution in which the luminescent metal complex is dissolved in an organic solvent, it is difficult to prepare an electroluminescent device that functions sufficiently. Therefore, when the luminescent metal complex used in the present invention is poorly soluble in halogenated hydrocarbon and aromatic organic solvents, the present invention can be more effectively effective. The luminescent metal complex used in the present invention preferably has a solubility in chloroform of less than 5 g / 100 g-CHCl3 at 22° C. The content of the luminescent metal complex in the aqueous dispersion of the present invention is preferably in the range of 1 to 50 mass%, more preferably in the range of 5 to 20 mass%.

[0025] The surfactant contained in the aqueous dispersion of the present invention is not particularly limited, and for example, a nonionic surfactant, an anionic surfactant, a cationic surfactant, an amphoteric surfactant, etc. Examples of the nonionic surfactant include a nonionic surfactant having no (poly)oxyethylene group and a nonionic surfactant having a (poly)oxyethylene group. Examples of nonionic surfactants not having a (poly)oxyethylene group include sorbitan fatty acid esters, fatty acid glycerides, and sucrose fatty acid esters. Examples of nonionic surfactants having a (poly)oxyethylene group include polyoxyethylene polyoxyalkylene alkyl ethers such as polyoxyethylene alkyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, and polyoxyethylene polyoxybutylene alkyl ethers; polyoxyethylene polyoxyalkylene alkenyl ethers such as polyoxyethylene alkenyl ethers, polyoxyethylene polyoxypropylene alkenyl ethers, and polyoxyethylene polyoxybutylene alkenyl ethers; polyoxyethylene fatty acid esters; aromatic nonionic surfactants such as ethylene oxide adducts of styrenated phenol, ethylene oxide adducts of benzylated phenol, and ethylene oxide adducts of p-cumylphenol; fatty acid alkanolamides; acetylene glycol surfactants; acetylene alcohol surfactants; and Pluronic surfactants.

[0026] Examples of the anionic surfactant that can be used include various fatty acid salts, alkylbenzenesulfonates, alkanesulfonates, alkyl sulfates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene-substituted phenyl ether sulfates, polycarboxylates, and the like, and counter ions include sodium, potassium, calcium, ammonium, triethanolamine, and the like.

[0027] Examples of the cationic surfactant that can be used include quaternary salts such as various alkyltrimethylammonium salts, alkyldimethylbenzylammonium salts, dialkyldimethylammonium salts, alkylpyridinium chloride salts, and quaternary polyoxyethylene alkylamines, as well as amine salts obtained by neutralizing amines with appropriate acids, such as alkylamine salts, alkyldimethylamine salts, and polyoxyethylene alkylamine salts. Examples of the counter ion include chloride ions, bromide ions, sulfate ions, formate ions, acetate ions, methyl sulfate ions, and ethyl sulfate ions.

[0028] Examples of amphoteric surfactants include alkylamine oxides, alanines, imidazolinium betaines, amido betaines, and betaine acetate. Specific examples include long-chain amine oxides, lauryl betaine, stearyl betaine, lauryl carboxymethyl hydroxyethyl imidazolinium betaine, lauryl dimethylamino acetate betaine, and fatty acid amidopropyl dimethylamino acetate betaine.

[0029] These surfactants may be used alone or in combination of two or more. The use of two or more surfactants in combination is preferable because it is possible to reduce the particle size of the luminescent metal complex used in the present invention in the aqueous dispersion of the present invention, thereby stabilizing the aqueous dispersion. In this case, the surfactant contains a nonionic surfactant and an anionic surfactant, and the amount of the nonionic surfactant in the surfactant is preferably 50% by mass or more, more preferably 70 to 95% by mass. In addition, it is preferable that the surfactant contained in the aqueous dispersion of the present invention is an ethylene oxide adduct of styrenated phenol, and when a nonionic surfactant and an anionic surfactant are used in combination, it is particularly preferable that the nonionic surfactant is an ethylene oxide adduct of styrenated phenol. Examples of the ethylene oxide adduct of styrenated phenol include polyoxyethylene monostyrenated phenyl ether (monostyrenated phenol ethoxylate), polyoxyethylene distyrenated phenyl ether (distyrenated phenol ethoxylate), polyoxyethylene tristyrenated phenyl ether (tristyrenated phenol ethoxylate), polyoxyethylene tetrastyrenated phenyl ether (tetrastyrenated phenol ethoxylate), polyoxyethylene pentastyrenated phenyl ether (pentastyrenated phenol ethoxylate), and mixtures thereof. Among these, polyoxyethylene tristyrenated phenyl ether or a mixture mainly composed of polyoxyethylene tristyrenated phenyl ether is preferred. Here, the term "mainly" means that it occupies 50% by mass or more of the mixture. In the aqueous dispersion of the present invention, the content of the surfactant is preferably 1 to 30 parts by mass relative to 100 parts by mass of the luminescent metal complex.

[0030] The aqueous dispersion of the present invention may contain any additives as long as the effects of the present invention are achieved. Examples of the additives include antifoaming agents, dispersants, rheology control agents, resin binders, colorants, antioxidants, ultraviolet absorbers, antibacterial agents, etc.

[0031] <Method of manufacturing aqueous dispersion> The method for producing the aqueous dispersion of the present invention includes a step of adding a surfactant and a solid luminescent metal complex to a medium mainly composed of water and dispersing the surfactant. The medium mainly composed of water, the luminescent metal complex, and the surfactant are as described above with respect to the form of the aqueous dispersion of the present invention. As described above, the luminescent metal complex used in the present invention is a solid that is insoluble in a medium mainly composed of water, and in the present invention, the luminescent metal complex is not dissolved in an organic solvent or the like to form an aqueous dispersion, so that the luminescent metal complex always maintains a solid state throughout the steps of the method for producing the aqueous dispersion of the present invention, even if the particle size changes.

[0032] In the method for producing the aqueous dispersion of the present invention, the order and timing of addition of the surfactant and the luminescent metal complex to the water-based medium are not important. The surfactant may be added to the water-based medium and mixed, and then the luminescent metal complex may be added and mixed, and then the dispersion process may be carried out. Alternatively, the luminescent metal complex may be added to the water-based medium and mixed, and then the surfactant may be added and mixed, and then the dispersion process may be carried out. In addition, the surfactant and the luminescent metal complex may be added in-line regardless of the order of addition while the water-based medium is circulated through the dispersion device, or the luminescent metal complex may be added in-line while the water-based medium to which the surfactant has been added and mixed in advance is circulated through the dispersion device. In order to increase the efficiency of the dispersion process, it is preferable to previously dry-grind the luminescent metal complex to make the particle size of the powder as small as possible when added to the water-based medium.

[0033] The dispersion step can be carried out by a conventionally known wet dispersion method. For example, a dispersion method using ultrasonic dispersion, a homomixer, a high-pressure homogenizer, a bead mill, a jet mill, a ball mill, an ultimaizer, etc. can be used, and a batch type treatment or a circulation type treatment can be appropriately carried out depending on the efficiency and processing amount of the dispersion step. In addition, a multi-stage dispersion treatment can be carried out by using the same dispersion method or different dispersion methods, or by changing the solid content concentration of the dispersion liquid.

[0034] Regarding the average particle size of the solid particles of the luminescent metal complex in the aqueous dispersion obtained by the method for producing an aqueous dispersion of the present invention, from the viewpoints of improving the stability over time of the aqueous dispersion (prevention of particle settling and maintenance of luminescent properties when used as an electroluminescent device, etc.), improving the coating property when forming a functional layer, and improving the surface properties of the functional layer, the dispersion should be carried out so as to be as small as possible, and the volume average particle size is preferably 500 nm or less, more preferably 200 nm or less. The volume average particle size can be determined by measuring the particle size distribution of the particle dispersion using a dynamic light scattering particle size distribution measuring device (for example, "NICOMP-380" (manufactured by Particle Sizing Systems, Inc.)) and analyzing it based on the Gaussian distribution. The average particle size of the solid particles of the luminescent metal complex is preferably 1 nm or more, since if it is too small, it may not be possible to expect a certain level of improvement in various properties compared to the energy cost required for the dispersion process.

[0035] <Electroluminescent device> The electroluminescent element of the present invention has, between a pair of electrodes, solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as a central metal, and a functional layer containing a surfactant (hereinafter also referred to as the "metal complex layer used in the present invention").

[0036] The layer structure of the electroluminescent element of the present invention may be a structure of a known organic EL element having various functional layers between a pair of electrodes (anode-cathode). For example, a structure in which a hole transport layer, a light emitting layer, and an electron transport layer are laminated in this order from the anode side, a structure in which the hole transport layer also serves as a light emitting layer, and a structure in which the electron transport layer also serves as a light emitting layer may be mentioned. A hole injection layer may be provided between the anode and the hole transport layer, and an electron injection layer may be provided between the cathode and the electron transport layer. Furthermore, a charge blocking layer or the like may be provided between the hole transport layer and the light emitting layer or between the light emitting layer and the electron transport layer.

[0037] These electrodes and various functional layers may have known compositions and configurations. For example, the anode may be made of metals such as gold, platinum, and palladium, or conductive transparent materials such as indium tin oxide (ITO), indium zinc oxide (IZO), SnO2, and ZnO, and the materials, including the substrates such as glass and plastic on which these materials are provided, are preferably transparent in the visible light range in order to extract light emission. The cathode may be made of metals such as tin, magnesium, indium, calcium, aluminum, and silver, or alloys thereof. For both the anode and the cathode, the sheet resistance is preferably several hundred Ω / □ or less, and the film thickness is appropriately adjusted accordingly.

[0038] Examples of the hole transport layer include a structure containing a hole transporting polymeric compound such as polyvinylcarbazole, or a hole transporting low molecular weight compound such as triphenylamines, stilbene derivatives, or oxadiazoles, together with a resin binder as necessary. The thickness of the hole transport layer is about 5 nm to 5 μm. Examples of the hole injection layer include a structure containing copper phthalocyanine, vanadium oxide, amorphous carbon, polyaniline, polythiophene, etc. Examples of the electron injection layer include a structure containing lithium fluoride, cesium fluoride, magnesium fluoride, aluminum oxide, etc. The thickness of these injection layers is about 0.1 nm to 5 μm.

[0039] In the electroluminescent device of the present invention, the metal complex layer is used as a light-emitting layer, an electron transport layer, or an electron transport layer that also functions as a light-emitting layer. The compositions in these layers and their preferred embodiments are as described above with respect to the form of the aqueous dispersion of the present invention. In this way, by configuring the light-emitting layer, the electron transport layer, or the electron transport layer that also functions as a light-emitting layer as described above, an electroluminescent device with excellent light-emitting properties can be obtained. There is no particular restriction on the film thickness of the light-emitting layer, the electron transport layer, or the electron transport layer that also functions as a light-emitting layer, but it is usually about 5 nm to 5 μm, preferably 5 to 200 nm.

[0040] <Method of manufacturing electroluminescent device> The method for producing an electroluminescence device of the present invention includes a step of forming a metal complex layer used in the present invention by coating or printing an aqueous dispersion containing solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as a central metal and a surfactant. The aqueous dispersion and its production method are as described above with respect to the form of the aqueous dispersion and its production method of the present invention.

[0041] In the manufacturing method of the electroluminescence element of the present invention, the aqueous dispersion of the present invention is applied or printed on a functional layer such as an electrode or a hole transport layer previously provided on the electrode to form a metal complex layer used in the present invention, thereby preparing an electroluminescence element. A known method can be used as the coating method, and examples thereof include a bar coating method, a dip coating method, a flow coating method, a spin coating method, a cast coating method, a roll coating method, a doctor blade method, and a spray method. A known method can also be used as the printing method, and examples thereof include a screen printing method, an offset printing method, a letterpress printing method, a gravure printing method, and an inkjet printing method. Depending on these coating methods or printing methods, the film thickness and surface properties to be obtained, the aqueous dispersion of the present invention can be used by appropriately adjusting its viscosity, solid content concentration, particle size of the luminescent metal complex, additives, and the like. EXAMPLES

[0042] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0043] <Ingredients description> [Luminescent metal complexes] Alq3: Tris(8-hydroxyquinolinolato)aluminum, manufactured by Tokyo Chemical Industry Co., Ltd. Solubility in chloroform at 22℃: 4.8g / 100g-CHCl3 Znq2 hydrate: Bis(8-hydroxyquinolinolato)zinc hydrate manufactured by Tokyo Chemical Industry Co., Ltd. Solubility in chloroform at 22℃: Less than 0.1g / 100g-CHCl3 Zn(btp)2: Bis(2-(2-benzothiazolyl)phenolato)zinc Manufactured by Tokyo Chemical Industry Co., Ltd. Solubility in chloroform at 22℃: 0.5g / 100g-CHCl3 Ir(dbfiq)2(bdbp): Bis(1-(dibenzo[b,d]furan-4-yl)isoquinolinolato)(1,3-bis(3,4-dibutoxyphenyl)propane-1,3-dionato)iridium Synthesized by the method described in Journal of Organometallic Chemistry, Volume 695, Issue 17, 1 August 2010, Pages 1972-1978. Solubility in chloroform at 22℃: 5.0g / 100g-CHCl3 or more [Nonionic surfactants] TSP: Ethylene oxide adduct of styrenated phenol (mixture of ethylene oxide adduct of styrenated phenol, mainly tristyrenated phenol ethoxylate), component concentration 100% by mass It is synthesized by adding ethylene oxide (molar number added: 17) to styrenated phenol, which is mainly tristyrenated phenol. [Anionic surfactants] PSCP: Styrenated cumylphenol ethoxylate sulfate ammonium salt, component concentration 100% by mass Synthesized by sulfuric acid esterification of ethylene oxide adduct of styrenated cumylphenol (mol number added: 26), mainly composed of pentastyrenated cumylphenol, with sulfamic acid. Teika Power (registered trademark) LN2050: Sodium linear alkylbenzene sulfonate, 50% by weight aqueous solution, manufactured by Teika Corporation [Cationic surfactants] -Cortamine (registered trademark) 86W: Stearyl trimethyl ammonium chloride, 28% by weight aqueous solution, manufactured by Kao Corporation [Antifoaming agent] ·DOWSIL® DK Q1-1183 Antifoam: Silicone-based antifoam agent Manufactured by Dow Toray Co., Ltd. [others] PVCz: Polyvinylcarbazole, weight average molecular weight 25,000-50,000, Merck CsF: Cesium fluoride manufactured by Alfa AESAR

[0044] <Measurement of solubility of luminescent metal complexes in chloroform> 0.25g of the luminescent metal complex and 5.0g of chloroform were added to a sealed glass container, and the container was shaken well. The container was then left to stand for 30 minutes at 22°C to prepare a saturated solution of the luminescent metal complex (if the luminescent metal complex is not completely dissolved, the undissolved portion of the luminescent metal complex is suspended). Next, the saturated solution was obtained by filtering the solution through a syringe filter with a pore size of 0.45μm to remove the undissolved luminescent metal complex. 3.0g of the saturated solution was precisely weighed into an aluminum cup, and the mass of the dried solid obtained by heating and drying the solution at 100°C for 1 hour using a hot air dryer was precisely weighed, and the solubility was calculated. Note that Ir(dbfiq)2(bdbp) was completely dissolved under the above conditions (solubility 5.0g / 100g-CHCl3 or more).

[0045] <Preparation and evaluation of aqueous dispersions> Example 1-1 1.00g of Alq3, 0.20g of TSP, 0.001g of DOWSIL DK Q1-1183 Antifoam, 8.00g of ion-exchanged water, and 10ml (apparent volume) of 0.5mmφ zirconia beads were added to a 100ml three-neck flask, and the mixture was stirred at 500 rpm for 12 hours with a stirrer equipped with a stirring blade to carry out a dispersion treatment. After that, the zirconia beads were filtered and separated to obtain an aqueous dispersion of Example 1-1.

[0046] Examples 1-2 to 1-7, Comparative Example 1-1 Except for changing the raw materials / usage amounts shown in Table 1, the same procedure as in Example 1-1 was carried out to obtain each of the aqueous dispersions of Examples 1-2 to 1-7 and Comparative Example 1-1.

[0047] Average particle size evaluation The above aqueous dispersions were diluted with distilled water to a measurable concentration, and the particle size distribution was measured using a dynamic light scattering particle size distribution analyzer "NICOMP-380" (Particle Sizing Systems, Inc.), and the volume average particle size (the average particle size of the solid particles of the luminescent metal complex) was calculated by analysis based on the Gaussian distribution. The results are shown in Table 1.

[0048] Evaluation of the average surface roughness of the coating film First, a toluene solution of PVCz (7 mg / ml) was spin-coated (1500 rpm (2 sec) → 3000 rpm (60 sec)) on the ITO layer of an ITO glass substrate (ITO layer thickness 150 nm, surface resistivity 10 Ω / □, manufactured by Sanyo Vacuum Co., Ltd.), and dried (120 ° C 1 hour) to form a PVCz layer with a thickness of 25 nm. On the layer, each aqueous dispersion diluted with ion-exchanged water to a solid content concentration of 6.4 mass% was spin-coated (1500 rpm (2 sec) → 3000 rpm (60 sec)), and dried (120 ° C 1 hour) to form a metal complex layer with a thickness of about 100 nm. Next, the surface shape of the metal complex layer surface in a range of 100 μm × 100 μm was measured using an atomic force microscope "Nanoscale Hybrid Microscope VN-8010" (manufactured by Keyence Corporation), and the average surface roughness based on JIS B 0601:2000 was calculated using the software attached to the device. The thickness of each functional layer, including the electroluminescent device described below, was determined by peeling a part of each functional layer from the ITO glass substrate, and measuring the height difference between the functional layer surface and the ITO glass substrate with the same atomic force microscope as above. The results are shown in Table 1.

[0049] [Table 1]

[0050] From the results in Table 1, comparing the Examples and Comparative Examples, it can be seen that the aqueous dispersion of the present invention has a good volume average particle size of 500 nm or less, and the average surface roughness of the coating film is small and good relative to the film thickness, so that a layer can be easily formed by a wet method. Also, comparing Example 1-1 with Example 1-2, it can be seen that the effects of the invention are more excellent when the surfactant contains a nonionic surfactant and an anionic surfactant, the amount of the nonionic surfactant in the surfactant is 50 mass% or more, and further, the nonionic surfactant is an ethylene oxide adduct of styrenated phenol.

[0051] <Fabrication and Evaluation of Electroluminescent Devices> Example 2-1 A toluene solution of PVCz (15 mg / ml) was spin-coated (1500 rpm (2 seconds) → 3000 rpm (60 seconds)) on the ITO layer (anode) of an ITO glass substrate (ITO layer thickness 150 nm, surface resistivity 10 Ω / □, manufactured by Sanyo Vacuum Co., Ltd.) that had been cleaned with a detergent and an organic solvent and then etched, and dried (120°C for 1 hour) to form a PVCz layer (hole transport layer) with a thickness of 60 nm. The aqueous dispersion of Example 1-1 diluted with ion-exchanged water to a solid content concentration of 4 mass% was spin-coated (1500 rpm (2 seconds) → 3000 rpm (60 seconds)) on the layer, and dried (120°C for 1 hour) to form a metal complex layer (X layer) with a thickness of 60 nm. Next, CsF (film thickness 1.0 nm, electron injection layer) and aluminum (film thickness 250 nm, cathode) were vacuum-deposited in this order on the metal complex layer, and then sealed with a UV-curable resin and a glass plate to obtain an electroluminescent device (organic EL device) of Example 2-1. In the electroluminescent device of Example 2-1, the X layer serves as an electron transport layer that also serves as a light-emitting layer.

[0052] Examples 2-2 to 2-6, Comparative Example 2-1 Each electroluminescence element of Examples 2-2 to 2-6 was obtained in the same manner as in Example 2-1, except that the aqueous dispersion of each Example or Comparative Example listed in Table 1 was used as the X-layer coating liquid by adjusting the solid content concentration so as to obtain the X-layer thickness listed in Table 2 or Table 3. In Comparative Example 2-1, the aqueous dispersion could not be applied, and therefore an electroluminescence element could not be obtained.

[0053] Examples 2-7 The electroluminescence device of Example 2-7 was obtained in the same manner as in Example 2-2, except that a toluene solution (15 mg / ml) in which PVCz and Ir(dbfiq)2(bdbp) were mixed and dissolved at a ratio of 10:1 (mass ratio) was used instead of the toluene solution of PVCz. In Example 2-7, the layer containing PVCz and Ir(dbfiq)2(bdbp) serves as a hole transport layer that also serves as a light emitting layer, and the X layer serves as an electron transport layer.

[0054] Comparative Example 2-2 A saturated chloroform solution of Alq3 was spin-coated on a PVCz layer formed on an ITO glass substrate in the same manner as in Example 2-1, but the PVCz layer was dissolved, making it impossible to obtain the desired electroluminescence device.

[0055] Comparative Example 2-3 A saturated chloroform solution of Alq3 was spin-coated (1500 rpm (2 sec) → 3000 rpm (60 sec)) onto the ITO layer of the same ITO glass substrate used in Example 2-1, and dried (120°C for 1 hr) to form an Alq3 layer with a thickness of 20 nm. Since the solubility of Alq3 in chloroform is low, the thickness of the Alq3 layer could not be increased beyond this. Next, CsF (thickness 1.0 nm) and aluminum (thickness 250 nm) were vacuum-deposited in this order onto the Alq3 layer, and then the resulting layer was sealed with a UV-curable resin and a glass plate to obtain an electroluminescent device of Comparative Example 2-3.

[0056] Comparative Example 2-4 An electroluminescent device of Comparative Example 2-4 was obtained in the same manner as in Example 2-1, except that the X layer was not provided.

[0057] Comparative Example 2-5 An electroluminescent device of Comparative Example 2-5 was obtained in the same manner as in Example 2-7, except that the X layer was not provided.

[0058] In Tables 2 and 3, the layer structure of each electroluminescent element is indicated by an abbreviation as the "element structure." For example, a layered structure in the order of a PVCz layer (hole transport layer), a metal complex layer (X layer), CsF (electron injection layer), and aluminum (cathode) from the ITO layer (anode) side is indicated as "ITO / PVCz / X / CsF / Al." When the PVCz layer contains Ir(dbfiq)2(bdbp), the layer is indicated as "PVCz:Ir(dbfiq)2(bdbp)."

[0059] Evaluation of the light-emitting performance of electroluminescent devices A voltage of 20 V was applied between the electrodes (anode-cathode) of each electroluminescent element to cause the electroluminescent element to emit light, and the color tone of the emitted light was judged visually, and the maximum brightness was measured using a brightness distribution characteristic measuring device "C9920-11" (manufactured by Hamamatsu Photonics K.K.). The observation surface was the ITO glass substrate side. The results are shown in Tables 2 and 3.

[0060] [Table 2]

[0061] [Table 3]

[0062] From the results of Tables 2 and 3, comparing the Examples and Comparative Examples, it can be seen that by preparing an electroluminescence element using the aqueous dispersion of the present invention, even when a luminescent metal complex that is poorly soluble in an organic solvent is contained, a layer can be easily formed by a wet method, and an electroluminescence element with excellent luminescence characteristics can be obtained. Also, comparing Example 2-1 and Example 2-2, it can be seen that the effect of the invention is more excellent when the surfactant contains a nonionic surfactant and an anionic surfactant, the amount of the nonionic surfactant in the surfactant is 50 mass% or more, and the nonionic surfactant is an ethylene oxide adduct of styrenated phenol.

Claims

1. An aqueous dispersion containing solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as a central metal, and a surfactant, The aqueous dispersion contains a nonionic surfactant and an anionic surfactant, and the amount of the nonionic surfactant in the surfactant is 50 mass % or more.

2. An electroluminescence device having a functional layer between a pair of electrodes, the functional layer containing solid particles of a luminescent metal complex having aluminum, zinc or a platinum group element as a central metal, and a surfactant, The electroluminescent device, wherein the surfactant contains a nonionic surfactant and an anionic surfactant, and the amount of the nonionic surfactant in the surfactant is 50 mass % or more.

Citation Information

Patent Citations

  • Fine particle dispersion, organic el element material, organoelectroluminescent element, display and illumination apparatus

    JP2006096697A

  • Organic electroluminescent element and its manufacturing method

    JP2007080677A

  • Coating dispersion liquid for organic electroluminescent element, nonaqueous coating dispersion liquid for organic electroluminescent element, organic electroluminescent element, display device, and lighting system

    JP2007165231A

  • Aqueous dispersion for manufacturing electronic device

    JP2010067870A

  • Electroluminescent formulation

    JP2013515360A